Molecular Detection of Porcine Torovirus in Piglets with Diarrhea in Southwest China - Yuancheng Zhou; Lei Chen; Ling Zhu; Zhiwen Xu (The Scientific World Journal)
Porcine torovirus (PToV) was detected from intestinal samples of piglets with diarrhea from 20 farms in southwest China. The total prevalence of PToV was 45% (9 out of 20 farms); it was the first detection of PToV in China, and also the study analyzed the phylogenetic relationships between the Chinese PToV and PToV reference strains as well as other representative toroviruses. Genetic and phylogenetic analysis showed the existence of genetic diversity among geographically separated PToV. Statistical analysis of the PToV positive rate as well as a survey for other enteric pathogens in diarrheic pigs suggests that PToV may play a role as a causative agent of severe diarrhea in piglets.